Malcolm X : by any means necessary : a biography - Myers, Walter Dean, 1937- (New York : Scholastic, 1993)
Few men in American history are as controversial as Malcolm X. In this provocative biography, Myers, winner of a Newbery Honor and four-time Coretta Scott King Award winner, presents a forthright portrait of a complex man whose life reflected the major events of our times.
Includes bibliographical references (p. 199-[200]) and index.
G12
Keywords: X, Malcolm, -- 1925-1965 -- Juvenile literature; X, Malcolm, -- 1925-1965.; Black Muslims -- Biography -- Juvenile literature; African Americans -- Biography -- Juvenile literature; Black Muslims; African Americans -- Biography